THE DEVELOPMENT OF THE NOKESO TEETH-MODIFYING TRADITION AMONG THE KAILI COMMUNITY IN PELAWA BARU VILLAGE - Hayatul Husna (Journal of Education and Teaching Learning, 2026)
This study aims to determine the development of the Nokeso tooth-cutting tradition among the Kaili people in Pelawa Baru Village and to identify the factors influencing changes in its practice. This study employs a qualitative research method with a descriptive approach. The informants in this study consist of the village head, customary leaders, community leaders, and community members who are knowledgeable about and have been involved in the execution of the Nokeso tradition. Data collection techniques were conducted through observation, interviews, and documentation. Based on the research results regarding the development of the Nokeso tooth-cutting tradition among the Kaili people in Pelawa Baru Village, the researcher concludes that the Nokeso tradition is a cultural heritage of the Kaili community that is still recognized and respected today as part of their cultural identity. However, throughout its development, the tradition has undergone changes marked by a decline in frequency, the simplification of customary procession stages, reduced community involvement, and a diminishing number of traditional leaders or sando who fully comprehend the complete procedures. These changes are influenced by shifts in the community's way of life, advancements in education and technology, evolving religious understanding, a shortage of practicing sando, and low youth engagement in preserving the tradition. Nevertheless, the community still views the Nokeso tradition as a symbol of maturity, respect for tradition, and a cultural heritage possessing values of culture, togetherness, responsibility, respect for parents, and cultural preservation that need to be maintained amidst modern developments